X-RAY MAMMOGRAPHY IN DIFFERENCES BETWEEN MASTITIS AND INFLAMMATORY BREAST CANCER - Fayzullaeva Madina Bakhshullo kizi; Boysariyeva Marjona Ravshan kizi; Norboeva Munisa Orif kizi; Nazrullayeva Nodira Najmiddin kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Breast cancer is more common in women over the age of 45. Infiltrative breast cancer accounts for 1-5% of all breast cancers. This article reviews the diagnosis of infiltrative breast cancer, mammography and sonoscopy, and the differential diagnosis with mastitis.